Bridging Generation Gaps Through Service-Learning in Higher Education: A Systematic Review - Aláez, Marian; Díaz-Iso, Ariane; Eizaguirre, Almudena; García-Feijoo, María (Frontiers in Education, 2022)
Advances in health care have led to an increased life expectancy for the older populations. An increasing body of research warns of the need to provide opportunities for older people to develop their potential for physical, mental, and social well-being during the aging process. In this context, universities have incorporated the service-learning (SL) methodology into their curricular and extracurricular programs. They attempt to offer their students experiences that allow them, from their experience and reflection, to advance in knowledge, skills and attitudes toward the older population group. Therefore, this methodology allows linking academic activities with social commitment, involving young people, as genuine agents of social change, in constructing a fairer, more inclusive, and supportive society. Despite the large body of research on the definition and benefits that students generally derive from SL, there are no systematic reviews of the full range of benefits that SL experiences, specifically with older people, provide to all participants. In this context, a rigorous systematic review was conducted by referring to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement and based on Web of Science (WoS), Scopus, and Education Resources Information Center (ERIC) databases, to answer one research question: What benefits do SL experiences that engage university students with older people, provide to the groups of participants? The analysis of the 28 selected research papers provides insights into the academic literature on the benefits of such experiences. On the one hand, they refer to the integral development of the student. On the other hand, they refer to the intergenerational relationships that promote the well-being of the elderly. Finally, the ethical commitment of the university, residences, agencies, and other organizations is mentioned. As a result, the positive impact on the community is highlighted.